Team adaptation to electronic communication media: Evidence of compensatory adaptation in new product development teams - Kock, Ned Florencio; Lynn, Gary S.; Dow, Kevin E.; Akgün, Ali Ekber (Palgrave Macmillan Ltd., 2006)
Prior research on the use of electronic communication media by teams performing complex tasks has led to contradictory findings. Much research has suggested that electronic communication media, due to not incorporating important elements found in face-to-face communication, pose obstacles for communication in comparison with the face-to-face medium. On the other hand, research has also suggested that teams interacting primarily electronically could perform quite well, sometimes even better, than face-to-face teams. A new theoretical framework, which builds on the notion of compensatory adaptation, has recently been advanced to explain these contradictory findings, arguing that (a) electronic communication media do pose obstacles to communication, and (b) individuals working in teams often compensate for obstacles posed by electronic communication media, which sometimes leads to team outcomes that are just as good or even better than those achieved by similar groups interacting primarily face-to-face. This study tests compensatory adaptation theory through a survey of 462 new product development teams, and finds general support for the theory. Important implications for research and practice are also discussed. © 2006 Operational Research Society Ltd. All rights reserved. © 2020 Elsevier B.V., All rights reserved.
Keywords: Collaborative technologies; Computer-mediated communication; Electronic communication; Knowledge sharing; New product development